Reaction of vegetative nervous system to loads in female long-distance runners with different fitness level - Bakayev, V.; Bolotin, A.; You, C. (Journal of Human Sport & Exercise, 2018)
In the course of research it was established that the female runner A with the high degree of vegetative nervous system parasympathetic division activity and the low degree of activity of the central regulation mechanisms with the increased activity of subcortical nervous centres had considerable advantage over the female runner B with high activity of the vegetative nervous system sympathetic division. The high activity of the central control structures taking into account the increased vegetative nervous system parasympathetic division activity in the female runner A indicates the high reserve capacity of the organism and the economical energy consumption during the running loads. It was revealed that the dynamics of heart rate regulation after the functional tests with physical loads is manifested in the change of the vegetative nervous system parasympathetic division tonicity. It affects the time-period of respiratory waves manifestation. The female runner A with the high fitness degree demonstrated the decreasing time-period compared to the female runner B with the low level of fitness